205k views
5 votes
What is the step by step solution to −2(1 − 4x) = 3x + 8

User Miebster
by
4.9k points

1 Answer

1 vote


\text {To solve this problem here's what you do}


\text {Simplify the equation:}


\text {(-2)(1)+(-2)(-4x)=3x+8 (Distribute)}


\text {-2+8x=3x+8}


\text {8x-2=3x+8}


\text {Now you will want to Subtract 3x:}


\text {8x-2-3x=3x+8-3x}


\text {5x-2=8}


\text {Next Step is to Add 2:}


\text {5x-2+2=8+2}


\text {5x=10}


\text {Final Step is to Divide 5:}


\text {5x/5=10/5}


\text {Your answer will be:}


\framebox {x=2}


\text {Hope this helps!}


\text {-LimitedX}

User Danle
by
4.1k points